Media Berbentuk Katalog PT. Polymindo Permata Kota Tangerang Penunjang Informasi Dan Promosi - Mukti Budiarto; Muhammad Arief (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
PT Polymindo Permata Tangerang which is new and still use the spoken and written media, exhibitions, events and websites but the less effective media to inform and introduce PT Polymindo Permata Tangerang city, PT. Polymindo jewel of the Tangerang city requires media catalog to support various activities such as informing the public at large. On the concept of there stages of Rough Layouts, Konferenship Layouts, Layout So. In order to produce an interesting catalogue of media design and quality used applications supporting Adobe Illustrator CC, then from it because the author does the design needs of media catalog.